Conceptual provisions of innovation marketing - Tkachova, N. P.; Matrosova, V. O.; Veryutina, V. O.; Pererva, P. G. (My University, 2022)
It has been proven that the marketing of innovations should be understood as activities aimed at finding new directions and ways of using the company's potential, developing new products and technologies on this basis, and promoting them to the market in order to more effectively meet the needs of consumers. way than competitors, thereby making a profit and providing conditions for long-term survival and development in the market.
Концептуальні положення маркетингу інновацій
Keywords: innovation marketing; market; intellectual property; demand; supply; industrial enterprises